A Regulatory Compliance Model for Financial Reporting Across Global Supply Chain Functions - John Oluwaseun Olajide,; Bisayo Oluwatosin Otokiti,; Sharon Nwani,; Adebanji Samuel Ogunmokun,; Bolaji Iyanu Adekunle,; Joyce Efekpogua Fiemotongha, (International Journal of Scientific Research in Science and Technology, 2024)
Global supply chains are increasingly complex, spanning multiple jurisdictions and regulatory environments, which presents significant challenges for financial reporting and compliance. This paper proposes a comprehensive regulatory compliance model tailored to financial reporting functions within global supply chain operations. Through a combination of literature review, theoretical modeling, and comparative analysis, the study examines key international financial regulations, including IFRS, GAAP, and SOX, and highlights the compliance difficulties associated with multi-jurisdictional operations such as regulatory fragmentation, inconsistent data governance, and sector-specific obligations. The paper also addresses the integration of financial controls into procurement and logistics, standardization of financial documentation, and implementation of risk-based auditing mechanisms using advanced technologies like blockchain and ERP systems. Central to the study is the development of a conceptual compliance model that incorporates legal, financial, and supply chain management functions into a unified framework. The model emphasizes core architectural elements including governance layers, feedback loops, and modular adaptability, enabling scalability across different organizational sizes and regulatory regimes. Technological enablers such as AI for anomaly detection and cloud-based platforms for global integration are explored as critical tools for real-time compliance management. The paper concludes by outlining the model’s implications for corporate governance, strategic transparency, and ethical operations, and offers directions for future empirical research and AI-enabled regulatory forecasting. This model represents a significant step toward harmonizing global financial compliance standards within supply chain ecosystems and strengthening financial integrity at both corporate and systemic levels.
Keywords: Regulatory Compliance; Financial Reporting; Global Supply Chains; Corporate Governance; Risk-Based Auditing; Compliance Model Integration